The Lyrical Relationship of Religious Music in the Post-Reformation Romantic Period, Using Bruckner's Mass No.3 in F Minor As an Example - Zhang, Xintian (Cultural Arts Research and Development, 2022)
As a composer who remained true to traditional style and compositional rigour during the Romantic period, Bruckner's work is permeated with both religious ethics and Romantic catharsis. It adds a unique dimension to the religious music of the Romantic period.